Effects of strength training on endurance capacity in top-level endurance athletes - Aagaard, P.; Andersen, J. L. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The effect of concurrent strength (S) and endurance (E) training on adaptive changes in aerobic capacity, endurance performance, maximal muscle strength and muscle morphology is equivocal. Some data suggest an attenuated cardiovascular and musculoskeletal response to combined E and S training, while other data show unimpaired or even superior adaptation compared with either training regime alone. However, the effect of concurrent S and E training only rarely has been examined in top-level endurance athletes. This review describes the effect of concurrent SE training on short-term and long-term endurance performance in endurance-trained subjects, ranging from moderately trained individuals to elite top-level athletes. It is concluded that strength training can lead to enhanced long-term (>30 min) and short-term (<15 min) endurance capacity both in well-trained individuals and highly trained top-level endurance athletes, especially with the use of high-volume, heavy-resistance strength training protocols. The enhancement in endurance capacity appears to involve training-induced increases in the proportion of type IIA muscle fibers as well as gains in maximal muscle strength (MVC) and rapid force characteristics (rate of force development), while likely also involving enhancements in neuromuscular function.